Beautifying a country home - Cook, Ida E. (My University, 1907)
Introduction: He who has the privilege of laying out home grounds should consider the work as an art - for it demands quite as much in the way of aesthetic feeling, creative power and executive skill as does the art of sculpture and painting. This is the art which creates beautiful cornposition upon the surface of the ground. We are the painters with the earth as our canvas. It differs from the other arts, in that it uses the same materials as nature herself, as been said: - "This is an Art Which does mend Nature; change it rather but "The Art itself is nature". We see man producing many effects which, under favorable conditions nature herself might have produced without the aid of man. Home should stand for harmony, order, neatness and contentment. In order to have these we must study our surroundings and the materials we have to work with.
Citation: Cook, Ida E. Beautifying a country home. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Country Homes; Home Improvement; Landscaping; Theses